Spectral story in Al_Farazdaq’s poetry - متوج حنين; عدنان أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research focuses on studying the spectral story in Al-Farazdaq’s poetry, and an attempt to show the images of the spectrum and how to use it. Al-Farazdaq was not the first to deal with the spectrum in poetry. Poets in the pre-Islamic era excelled in using the spectrum, and employing it in expressing their psychological, social and emotional conditions, but the most beautiful thing that Al-Farazdaq added to the story of the spectrum is the emotion of nostalgia that he transmitted in it. So, it is a small flame of precious and radiant feelings, and the follower of Al-Farazdaq’s poems notices that he was able, through the spectral story, to create a new reality for him to seek refuge and to resort to, to get rid of the feeling of affliction and deprivation he suffers from, in a narrative direction that focuses on elucidating the images of life, and monitoring its details in an artistic style that attracts the reader and excites And he seems interested in the elements of the story such as narration, dialogue, characters, event, time and place, and he also expresses through spectral stories the astonishment at the ability of the spectrum to reach the poet, surviving all the difficulties and dangers that surround the journey without a guide to guide him or a helper to support him.